Production analysis of corn farming (Zea mays L) in the Bumi Beringin Village, North Luwuk District, Banggai Regency - Femiyanti Djamaludin; Yuni Rustiawati; Ruslan Zaenuddin (CELEBES Agricultural, 2021)
Corn is a food commodity that is widely cultivated in Bumi Beringin Village. To get high corn production, it is necessary to utilize optimal production factors. This study aims to determine the effect of land area, the number of seeds, amount of fertilizer, and number of workers on maize production (Zea mays L), and the correlation between maize farming in Bumi Beringin Village, North Luwuk District. This research was carried out from March to May 2021. The respondents' determination was carried out using a saturated sampling method or census where 22 farmers did corn farming. The analysis used is the Cobb-Douglas production function with variables of land area (X1), the number of seeds (X2), amount of fertilizer (X3), and number of workers (X4), and corn production (Y). The analysis results obtained multiple correlation coefficient values of 0.99%, indicating that corn production with production factors (land area, seeds, fertilizers and workers) has a very strong relationship with a relationship level of 99%.